2013
DOI: 10.1084/jem.20122344
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of stromal cells expressing fibroblast activation protein-α from skeletal muscle and bone marrow results in cachexia and anemia

Abstract: Ablation of stromal cells expressing fibroblast activation protein-α (FAP) results in cachexia and anemia, and loss of these cells is seen in transplantable tumor models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
290
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 327 publications
(314 citation statements)
references
References 49 publications
(78 reference statements)
8
290
1
Order By: Relevance
“…Another study assessing colorectal patients receiving 131 Ilabeled anti-FAP antibody reported no uptake by normal tissues, which was interpreted as indicating that the FAP protein was absent from normal tissues (40). Therefore, it was surprising when the bioluminescent signal of BAC transgenic mice in which the fap gene controlled expression of luciferase was demonstrated in almost all tissues of the (41). FAP þ cells of skeletal muscle are the major local source of follistatin, which is required to maintain muscle mass by inhibiting myostatin and activin A signaling in this tissue.…”
Section: Studies Of the Fap þ Stromal Cell In Normal Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study assessing colorectal patients receiving 131 Ilabeled anti-FAP antibody reported no uptake by normal tissues, which was interpreted as indicating that the FAP protein was absent from normal tissues (40). Therefore, it was surprising when the bioluminescent signal of BAC transgenic mice in which the fap gene controlled expression of luciferase was demonstrated in almost all tissues of the (41). FAP þ cells of skeletal muscle are the major local source of follistatin, which is required to maintain muscle mass by inhibiting myostatin and activin A signaling in this tissue.…”
Section: Studies Of the Fap þ Stromal Cell In Normal Tissuesmentioning
confidence: 99%
“…For example, FAP þ cells are altered in skeletal muscle and the bone marrow in transplantable and spontaneous mouse models of cancer-induced cachexia and anemia, suggesting that they may have roles in these poorly understood cancer-induced syndromes (41). Fortunately, the discovery of the FAP þ lineage and its essential homeostatic functions occurred before the consideration of depleting FAP þ cells, as a means for overcoming tumoral immune suppression had advanced to a human clinical program.…”
Section: Studies Of the Fap þ Stromal Cell In Normal Tissuesmentioning
confidence: 99%
“…We previously described a bacterial artificial chromosome (BAC) transgenic (Tg) mouse line (DM2) (21) in which the fap gene in the BAC has been modified by the insertion of a cassette composed of the coding sequences of the primate diphtheria toxin (DTX) receptor (DTR) and firefly luciferase. In this Tg mouse, fap-driven luciferase expression was detected in the inguinal LN (iLN) but not the spleen, consistent with the relative levels of Fap mRNA in these tissues (Fig.…”
Section: Ln Frcsmentioning
confidence: 99%
“…Whereas FAP −/− mice are phenotypically indistinct from wild-type mice (18), the stromal cell that expresses FAP mediates immune suppression in the tumor microenvironment (19,20) and maintains skeletal muscle mass and hematopoiesis (21,22). FAP + stromal cells from different organs display similar gene expression profiles, but adopt organ-specific functions, like the production of specific cytokines and chemokines.…”
mentioning
confidence: 99%
See 1 more Smart Citation